Selective root canal retreatment of a maxillary first molar: a case report with a 9-year follow up - Guerreiro Viegas, Olavo; Santos, João Miguel Marques (Frontiers in Dental Medicine, 2024)
Traditional endodontic retreatments usually target the entire root canal system. In contrast, selective root canal retreatment presents a new, targeted alternative that offers a less invasive solution. However, its promising approach faces potential obstacles due to a lack of long-term data, which might affect its widespread acceptance. This case report adds to the existing body of literature by offering an in-depth analysis of a long-term outcome following selective non-surgical retreatment, thereby bridging an important gap in knowledge. A 59-year-old male presented with post-treatment apical periodontitis (PTAP) in a maxillary first molar. Initial clinical examination revealed the patient was symptomatic, and the tooth responded negative to thermal tests and positive to vertical percussion. Radiographic assessment identified a radiolucency confined to the mesiobuccal root. No radiolucencies or signs of inflammation were observed in the distobuccal and palatal roots. These findings led to the decision to selectively retreat the mesiobuccal root non-surgically. This targeted approach aimed at addressing the inflammation while preserving the integrity of unaffected areas. The patient received selective non-surgical retreatment on the mesiobuccal root. During a nine-year follow-up, the patient remained asymptomatic, as confirmed by clinical observation. Periapical radiograph and Cone Beam Computed Tomography (CBCT) scan demonstrated complete healing of the treated root. Importantly, the untreated roots showed no signs or symptoms of apical periodontitis. This underscores the efficacy of the targeted treatment and its successful resolution of the inflammation. This case report aimed to show the long-term effectiveness and minimally invasive nature of selective root canal retreatment to address PTAP. It focused on the method's capacity to preserve tooth structure with minimum intervention. The positive outcomes highlight the urgent need for more controlled studies. Such research would confirm the advantages of selective retreatment, with the goal of improving endodontic protocols and patient care.